A multidão de solitários: a solidão na filosofia de Friedrich Nietzsche - Santos, Bárbara Raffaelle Carvalho (2022)
The objective of this dissertation is to analyze the importance of solitude in Nietzsche's philosophy and its dimensions. We can interpret it in at least three instances (I) as a counterpoint to the market and the excessive noise of theoretical men, being a moral disengagement (II) as part of the reaffirmation of the multitude and the denial to the body, as a way of enhancing metaphysics and the denial of the body, (III) part of the experience of creating aesthetically, in other words, affirmation of life and invention of meanings that exalt the body. We will mainly use the works Aurora, On the genealogy of morals and Thus spoke Zarathustra to understand the theme of loneliness in philosophical conceptions, in addition to Ecce Homo together with excerpts from the author's correspondence to understand loneliness as an existential phenomenon. Nietzsche experienced solitude making his philosophy a way of life and not just a conceptual abstraction. Loneliness permeates the criticism of culture and morality and is seen as a continuous process of overcoming, a way of cultivating a new human feeling that goes beyond metaphysics. Therefore, solitude is a condition of possibility for overcoming decadence, a form of self-affirmation that goes beyond the morality consolidated in the reactive bases of the herd.